RISK MANAGEMENT (RM) PRACTICE OF UABEKISTAN AIRWAYS COMPANY - Vafokulova Mekhruza Sukhrobjon kizi (Scholars Digest Publishing, 2023)
National Air Company Uzbekistan Airways, operating, as Uzbekistan Airways is the flag carrier airline of Uzbekistan, headquartered in Tashkent. From its hub at Tashkent International Airport, the airline serves a number of domestic destinations; the company also flies international services to Asia, Europe and North America. Uzbekistan airways Company had a flight accident in 2004. The flight was Uzbekistan Airways Yakovlev-40. Moreover, because of the accident 37 people died. Overall, eight accidents the airline company experienced. Since then company is trying to restore and regain its status. The reason of the choice of this company to see how the company is improving or changing its risk management policy.
Keywords: airline, company, risk, management.